2023
DOI: 10.1111/rda.14435
|View full text |Cite
|
Sign up to set email alerts
|

Canine prostatic serum esterase and strain and 2D‐shear wave sonoelastography for evaluation of normal prostate in dogs: Preliminary results

Abstract: Canine prostatic serum esterase (CPSE) is considered a useful tool to identify prostate disorders in dogs, with increasing interest in ultrasound (US)‐based sonoelastography to non‐invasively detect prostate disorders. Since no report is available about a possible correlation between these diagnostic tools, we aimed to investigate a possible correlation between strain elastography (SE) and 2D‐shear wave elastography (SWE) and CPSE. Twenty‐one dogs were included and, on each animal, CPSE was evaluated followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Third, it can be used to diagnose various soft tissue diseases. A small number of studies have confirmed that 2D-SWE can measure tissue stiffness in organs such as the spleen, kidneys, and prostate [22,39,40]. All of the above suggests that 2D-SWE is an excellent diagnostic imaging tool with great clinical potential in veterinary medicine.…”
Section: Discussionmentioning
confidence: 95%
“…Third, it can be used to diagnose various soft tissue diseases. A small number of studies have confirmed that 2D-SWE can measure tissue stiffness in organs such as the spleen, kidneys, and prostate [22,39,40]. All of the above suggests that 2D-SWE is an excellent diagnostic imaging tool with great clinical potential in veterinary medicine.…”
Section: Discussionmentioning
confidence: 95%
“…For prostate evaluation, the B-mode ultrasound is certainly the technique of choice, allowing the evaluation of both the dimensions and the characteristics of the parenchyma [ 10 , 18 ]. In addition to the B-mode exam, further ultrasound methods are available for increasingly detailed and early information, such as the Doppler exam, which allows the evaluation of prostatic vascularization and blood flow [ 19 ], and, recently, also the strain and 2D-shear wave elastography technique, described for the study of the prostatic tissue elasticity [ 20 ]. Recently, the contrast-enhanced ultrasound (CEUS) has become an increasingly useful tool in veterinary medicine to identify organ perfusion and vascularization [ 21 ].…”
Section: Introductionmentioning
confidence: 99%